1988
DOI: 10.1123/jsep.10.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Do Anxious Swimmers Swim Slower? Reexamining the Elusive Anxiety-Performance Relationship

Abstract: The purpose of this investigation was to utilize a multidimensional measure of anxiety and a more sensitive intraindividual performance measure to evaluate the relationship between anxiety and performance. Three hypotheses were tested. First, cognitive anxiety is more consistently and strongly related to performance than is somatic anxiety. Second, somatic anxiety demonstrates an inverted-U relationship with performance, whereas self-confidence and performance exhibit a positive linear relationship and cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
2
31

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(152 citation statements)
references
References 12 publications
8
108
2
31
Order By: Relevance
“…Mientras que quienes se esfuerzan por la impecabilidad en competición, pero mayormente se enfocan en ganar o mostrar superioridad, manifiestan más pensamientos e imágenes negativas sobre el desempeño, conduciendo a experimentar preocupación, temor e inseguridad en su rendimiento, y por tanto dificultad en la atención (Burton, 1988). Ello confirmado a partir del análisis de mediación.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Mientras que quienes se esfuerzan por la impecabilidad en competición, pero mayormente se enfocan en ganar o mostrar superioridad, manifiestan más pensamientos e imágenes negativas sobre el desempeño, conduciendo a experimentar preocupación, temor e inseguridad en su rendimiento, y por tanto dificultad en la atención (Burton, 1988). Ello confirmado a partir del análisis de mediación.…”
Section: Discussionunclassified
“…https://doi.org/10.5232/ricyde2018.05205 Por otra parte, la orientación al ego es a veces considerada como una orientación motivacional disfuncional, particularmente en combinación con baja orientación a la tarea (Duda, 2005), por lo que puede conducir a la ansiedad. La ansiedad estado competitiva es un estado emocional caracterizado por sentimientos de aprensión, tensión y activación en situaciones competitivas (Martens, Vealey, y Burton, 1990), la cual puede afectar el rendimiento deportivo (Burton, 1988;Smith, Smoll, y Schutz, 1990). …”
Section: Introductionunclassified
“…Concerning the relationship between cognitive anxiety and performance, research has found a negative relationship involving these variables. Higher levels of cognitive anxiety are associated with lower levels of performance (Burton, 1988;Motowildo, Packard, &Manning, 1986). Klein (1990) by using the technique of meta-analysis concluded the negative relationship of anxiety and performance is: a) stronger in female athletes …”
Section: Anxietymentioning
confidence: 99%
“…Understanding the various manifestations of the anxiety is important to comprehend their influence on performance. A negative linear relationship with CA and a positive linear relationship with their personal capacity has been proved in relation to physical performance [62]. The SA also has a greater negative impact on events of short duration.…”
Section: Discussionmentioning
confidence: 89%